Traditional and Current Food Use of Wild Plants Listed in the Russian Pharmacopoeia - Shikov, Alexander N.; Tsitsilin, Andrey N.; Pozharitskaya, Olga N.; Makarov, Valery G.; Heinrich, Michael (Frontiers in Pharmacology, 2017)
Historically Russia can be regarded as a ‘herbophilious’ society. For centuries the multinational population of Russia has used plants in daily diet and for self medication. The specificity of dietary uptake of medicinal plants (especially those in the unique and highly developed Russian herbal medical tradition) has remained mostly unknown in other regions. Based on 11th edition of the State Pharmacopoeia of the USSR, we selected 70 wild plant species which have been used in food by local Russian populations. Empirical searches were conducted via the Russian-wide applied online database E-library.ru, library catalogs of public libraries in St-Petersburg, the databases Scopus, Web of Science, PubMed, and search engine Google Scholar. The large majority of species included in Russian Pharmacopoeia are used as food by local population, however, aerial parts are more widely used for food. In this review, we summarize data on medicinal species published in Russia and other countries that are included in the Russian Pharmacopoeia and have being used in food for a long time. Consequently, the Russian Pharmacopoeia is an important source of information on plant species used traditionally at the interface of food and medicine. At the same time, there are the so-called "functional foods", which denotes foods that not only serves to provide nutrition but also can be a source for prevention and cure of various diseases. This review highlights the potential of wild species of Russia monographed in its pharmacopoeia for further developing new functional foods and – through the lens of their incorporation into the pharmacopoeia – showcases the species’ importance in Russia.